"Who Cares?": Investigating Consistency in Expressions of Racial Apathy among Whites. (May 2019) - Brown, Tony N.; Bento, Asia; Gorman, Quintin; Koku, Lydia; Culver, Julian
Survey researchers theorize that how whites express racial prejudice changes across time. They argue one of its contemporary forms is racial apathy (i.e., not caring about racial equality). However, few empirical studies characterize racial apathy. To fill this gap, the present study addresses consistency in racial apathy across time at the population level and individual level. Using three waves of panel data (i.e., 2003, 2007–2008, and 2013) from the National Study of Youth and Religion, the authors examine the distribution of racial apathy at each wave. The authors then cross-tabulate racial apathy at wave 1 and wave 3, wave 3 and wave 4, and wave 1 and wave 4. The authors next explore correlates of individual-level consistency in racial apathy across time. Results reveal strong population-level consistency concurrent with weak individual-level consistency in the distribution of racial apathy. Furthermore, few correlates predict individual-level consistency.